3D Ball Trajectory Reconstruction of a Ballistic Shot from a Monocular Basketball Video - Vanyi Chao; Ankhzaya Jamsrandorj; Yin May Oo; Mun, Kyung-Ryoul; Kim, Jin wook (Proceedings of IECON 2023, 2023)
3D ball location in sports can be advantageous and has many applications such as automatic scoring system, ball trajectory highlight and offside detection system for football game. Currently, this task can be solved through the use of costly multi-view approaches or the legacy physics-based methods that require complicated setups and human intervention. In this paper, we propose a method to reconstruct the 3D ball trajectory of the basketball projectile shot by using only a single view. The method relies on accurate camera calibration and 2D ball detection of sequence images. Extra information in the 3D world also plays an important role in improving the 3D reconstruction. The experimental result illustrates the accurately reconstructed 3D trajectory when enough information is given.